2019
DOI: 10.1101/760785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary and biochemical analyses reveal conservation of the Brassicaceae telomerase ribonucleoprotein complex

Abstract: AbstractThe telomerase ribonucleoprotein complex (RNP) is essential for genome stability and performs this role through the addition of repetitive DNA to the ends of chromosomes. The telomerase enzyme is composed of a reverse transcriptase (TERT), which utilizes a template domain in an RNA subunit (TER) to reiteratively add telomeric DNA at the ends of chromosomes. Multiple TERs have been identified in the model plant Arabidopsis thaliana. Here we com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
(2 reference statements)
1
7
1
Order By: Relevance
“…S1 B and C). These results are inconsistent with AtTER1 being a functional telomerase RNA and instead support the recent findings of Fajkus et al (34) and Dew-Budd et al (35) indicating that AtTER1 is not required for telomere maintenance.…”
Section: Resultscontrasting
confidence: 81%
See 1 more Smart Citation
“…S1 B and C). These results are inconsistent with AtTER1 being a functional telomerase RNA and instead support the recent findings of Fajkus et al (34) and Dew-Budd et al (35) indicating that AtTER1 is not required for telomere maintenance.…”
Section: Resultscontrasting
confidence: 81%
“…We previously described the identification of 2 telomeraseassociated RNAs from Arabidopsis thaliana, termed AtTER1 and AtTER2 (32,33). AtTER1 was proposed to serve as the template for telomeric DNA synthesis by telomerase (32); however, recent data have refuted the role of AtTER1 in telomere maintenance (34,35). Moreover, Fajkus et al (34) recently reported the identification of a novel telomerase RNA from A. thaliana, termed AtTR, that is required for telomere maintenance and is conserved across land plants.…”
Section: Significancementioning
confidence: 99%
“…As far as we know, there is still no data on any algal TR, which would elucidate whether Pol III transcription of TR is a general feature for all plants or not. This work (Fajkus et al, 2019), based on CRISPR knock-out and other experiments, also showed that a previously identified telomerase RNA candidate in A. thaliana (Cifuentes-Rojas et al, 2011;Beilstein et al, 2012) was not a functional template subunit of telomerase, as was also demonstrated shortly after by (Dew-Budd et al, 2019). Assuming that the Pol II/Pol III dependency for TR transcription is a reliable evolutionary marker, future TR research in other main eukaryotic lineages will probably open new insights into the origin of eukaryotes.…”
Section: What Are the Molecular Reasons For Changes In The Telomere Msupporting
confidence: 54%
“…The assembly was performed as stranded RNA-seq with paired-end fastq datasets. Putative TR from Z. marina were found out using blast with published orthologs 10,18,19 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a combination of the available genomic data from Alismatales with the recent breakthrough of the discovery of plant telomerase RNA10,18,19 have led us to the astonishing conclusion that the template region in plant telomerase RNA is a very dynamic element, with unexpectedly variable borders, even in species with the same telomere sequence. The finding of two distinct telomerase RNA paralogs within several of the Alismatales genomes analysed, including the Z. marina genome assembly, offers an answer to how plants are able to change their telomeres.…”
Section: The Telomere Template In Z Marina Telomerase Rna Helps Us Umentioning
confidence: 99%